2016
DOI: 10.1007/978-3-319-42059-2_1
|View full text |Cite
|
Sign up to set email alerts
|

Non-coding RNAs: Classification, Biology and Functioning

Abstract: One of the long-standing principles of molecular biology is that DNA acts as a template for transcription of messenger RNAs, which serve as blueprints for protein translation. A rapidly growing number of exceptions to this rule have been reported over the past decades: they include long known classes of RNAs involved in translation such as transfer RNAs and ribosomal RNAs, small nuclear RNAs involved in splicing events, and small nucleolar RNAs mainly involved in the modification of other small RNAs, such as r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
507
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 719 publications
(514 citation statements)
references
References 125 publications
2
507
0
5
Order By: Relevance
“…Many studies have demonstrated the diverse cellular functions of lncRNAs including cell proliferation, cell differentiation, cell apoptosis, and carcinogenesis [13]. Several studies demonstrated that circulating lncRNAs are potential diagnostic biomarkers for several types of cancer [14].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have demonstrated the diverse cellular functions of lncRNAs including cell proliferation, cell differentiation, cell apoptosis, and carcinogenesis [13]. Several studies demonstrated that circulating lncRNAs are potential diagnostic biomarkers for several types of cancer [14].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, with the advanced development of large‐scale technology, a growing number of observations have determined that numerous noncoding sequences occupy more than 90% of the human genome . Long noncoding RNAs (lncRNAs), as a class of the noncoding RNA molecules, are greater than 200 nucleotides in length with limited protein coding capacity .…”
Section: Introductionmentioning
confidence: 99%
“…In the past, lncRNAs were considered to be “evolutionary junk” or transcriptional “noise” along with other non-coding RNAs [2, 3]. However, in recent years, as the rapid development of technologies has facilitated analysis of the “transcriptome”, there is increasing evidence that lncRNAs play a crucial role in many biological processes [4, 5], such as telomere homeostasis and chromosome replication [68], control of nuclear architecture and translation [9], X-chromosome inactivation [10], regulation of epigenetic modifications [11], control of mRNA and protein stability [12, 13], and regulation of miRNA activity [14, 15]. As research into lncRNA increased, many databases were established and included lncRNA data for both domesticated animals and poultry.…”
Section: Introductionmentioning
confidence: 99%